Effect of balance perturbations in patients with cognitive impairment and normal ageing. Issue 1 (January 2019) - Marinelli, L.; Trompetto, C.; Puce, L.; Leandri, S.; Monacelli, F.; Leandri, M.
Abstract : Balance worsens with age and further deteriorates in subjects with cognitive impairment. Understanding the mechanisms underlying balance and their relation with ageing and cognition is crucial to plan exercise aimed at preventing falls. Aim of the study is to assess reaction to balance perturbations in a population of cognitive impaired subjects compared to controls. We recruited 10 patients with Alzheimer's disease, 9 with mild cognitive impairment, 12 age-matched and 10 young controls. Balance was recorded with a balance board, capable of high sampling rate acquisition of the center of pressure oscillations during static and dynamic conditions. All subjects underwent static acquisitions before and after 10 displacements induced by a slight board backward tilting. The sway path length was compared before and after displacements. Mild cognitive impairment and aged controls showed a longer sway path after a tilting session compared to baseline. Patients with Alzheimer's disease showed longer sway paths either before and after tilting. Young controls had a shorter sway path in both conditions. Patients with overt dementia show similar balance impairment at the static test either before or after tilting. Conversely, in aged subjects, balance is easily disrupted and probably recovers slowly compared to young subjects.